Thermal and Mechanical Properties of Geopolymers Exposed to High Temperature: A Literature Review - He, Rui; Wang, Zhenjun; Dai, Nan (Advances in Civil Engineering, 2020)
Geopolymers are prepared by alkali solution-activated natural minerals or industrial waste materials, which have been widely used as new sustainable building and construction materials for their excellent thermal and mechanical properties. The thermal and mechanical properties of geopolymers at high temperature have attracted great attention from many researchers. However, there are few systematic works concerning these two issues. Therefore, this work reviewed the thermal and mechanical behaviors of geopolymers at high temperature. Firstly, the thermal properties of geopolymers in terms of mass loss, thermal expansion, and thermal conductivity after high temperature were explained. Secondly, the mechanical properties of residual compressive strength and stress-strain relationship of fly ash geopolymers and metakaolin geopolymers after high temperature were analyzed. Finally, the microstructure and mineralogical characteristics of geopolymers upon heating were interpreted according to the changes of microstructures and compositions. The results show that the thermal properties of geopolymers are superior to cement concrete. The geopolymers possess few mass loss and a low expansion ratio and thermal conductivity at high temperature. The thermal and mechanical properties of the geopolymers are usually closely related to the raw materials and the constituents of the geopolymers. Preparation and testing conditions can affect the mechanical properties of the geopolymers. The stress-strain curves of geopolymer are changed by the composition of geopolymers and the high temperature. The silicon-type fillers not only improve the thermal expansion of the geopolymers but also enhance mechanical properties of the geopolymers. But, they do not contribute to reducing the thermal conductivity. the different raw materials, aluminosilicate precursor and reinforcement materials, result in different geopolymer damage during the heating. However, phase transitions can occur during the process of heating regardless of the raw materials. The additional performance enhancements can be achieved by optimizing the paste formulation, adjusting the inner structure, changing the alkali type, and incorporating reinforcements.